Evaluation of Wheat Genotypes under Timely and Late Sowing Conditions - Poudel, Padam Bahadur; Jaishi, Uttam Kumar; Poudel, Laxmi; Poudel, Mukti Ram (International Journal of Applied Sciences and Biotechnology, 2020)
A field experiment was conducted at Institute of Agriculture and Animal Science (IAAS), Bhairahawa during winter season of 2019/2020 to find out the performance of wheat genotypes under timely sown (November 29, 2019) and late sown (December 25, 2019) conditions. The research was carried out in two environments (timely sown and late sown) following alpha lattice design with two replications. Each replication consists of five blocks with four plots in each block. The results revealed that all genotypes performance was decreased in late sowing environment. In late sown condition, there was significant difference among genotypes for all the traits under study and under timely sown condition, there was significant difference among genotype for all traits under study except weight of grains per spike and grain yield. The maximum yield was recorded in NL 1179 and Bhirkuti in timely and late sown conditions respectively. It was found that the mean grain yield in timely sown condition is 90.77 % higher than in late sown condition. The maximum grain yield was recorded in NL 1179 across combine environment. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 161-169